The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s11661-007-9283-6
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Precipitation Strengthening in Dilute Al-Ti and Al-Zr Alloys

Abstract: Two conventionally solidified Al-0.2Ti alloys (with 0.18 and 0.22 at. pct Ti) exhibit no hardening after aging up to 3200 hours at 375°C or 425°C. This is due to the absence of Al 3 Ti precipitation, as confirmed by electron microscopy and electrical conductivity measurements. By contrast, an Al-0.2Zr alloy (with 0.19 at. pct Zr) displays strong age hardening at both temperatures due to precipitation of Al 3 Zr (L1 2 ) within Zr-enriched dendritic regions. This discrepancy between the two alloys is explained w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(57 citation statements)
references
References 62 publications
3
49
0
5
Order By: Relevance
“…Despite the fact that the solute concentration is above the maximum solvus composition of 0.24 at% reported for the metastable AlZr binary system, 28) the present combination of solute concentration and cooling rate suppresses the formation of the ¢A phase, known to act as grain refiner, and a supersaturated Al solid solution possessing a typical columnar solidification structure forms. This is in fact the ideal situation for an aged hardening alloy, 28) but is the worst condition in the situation to develop an alloy for nanostructured solidification grains. Figure 7(a) presents a back scattered micrograph of the Al¹1 at%Zr, showing a band-structure containing precipitates and a zone with a significantly lower precipitate concentration above.…”
Section: Microstructure Development During Esd Of Alzr Binary Alloysmentioning
confidence: 70%
“…Despite the fact that the solute concentration is above the maximum solvus composition of 0.24 at% reported for the metastable AlZr binary system, 28) the present combination of solute concentration and cooling rate suppresses the formation of the ¢A phase, known to act as grain refiner, and a supersaturated Al solid solution possessing a typical columnar solidification structure forms. This is in fact the ideal situation for an aged hardening alloy, 28) but is the worst condition in the situation to develop an alloy for nanostructured solidification grains. Figure 7(a) presents a back scattered micrograph of the Al¹1 at%Zr, showing a band-structure containing precipitates and a zone with a significantly lower precipitate concentration above.…”
Section: Microstructure Development During Esd Of Alzr Binary Alloysmentioning
confidence: 70%
“…The temperatures employed were 650 and 700 K, ±1K at the times of 4, 12, 24, 100 and 400 h. The aging temperatures and times were adopted because a study in the literature demonstrated that these parameters promote precipitation hardening in hiperperitectic Al-Zr alloys 4 . After the treatments, samples were water-quenched to room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In the latter as pylons and missile tail cones 2 . Al-Zr alloys are precipitation hardening and present elevated thermal stability due to the precipitation of nanometer-scale metastable Al 3 Zr L1 2 precipitates 1,3,4 . These particles are coherent, thermodynamically stable 5 and provide hardening even after long times of heat-treatment (400 h) at temperatures of 698 K 6 and nucleate homogeneously in a high number density at the center of the dendrites, where supersaturation is greater 4,6 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations